The clinical signs and risk factors of non-ambulatory children with cerebral palsy - Kułak, Wojciech; Okurowska-Zawada, Bożena; Sienkiewicz, Dorota; Paszko-Patej, Grażyna; Gościk, Elżbieta (Journal of Pediatric Neurology, 2011)
The aim of the study was to analyze the risk factors and clinical picture of cerebral palsy in non-ambulatory children. The study included 133 children (77 boys and 56 girls) with cerebral palsy aged 6– 17 years. The patients remained under the care of the Outpatient Clinic and Department of Pediatric Rehabilitation of the Medical University of Bialystok. Ninety-eight of the studied patients had spastic tetraplegia, 14 diplegia and 21 hemiplegia. The average duration of pregnancy was 35.21 ± 1.32 weeks, the mean Apgar score was 4.31 ± 3.60 and the mean birth weight was 2448.3 ± 384.7 g. The patients exhibited the following types of motor dysfunctions: spasticity was found in 91 (68.9%) of the patients, hypotonia in 24 (18.2%), extrapyramidal symptoms in 13 (9.8%) and ataxia in 4 (3.0%) cases. More than3/4 (79%) of the children were classified as level V on the Gross Motor Functional Classification System (GMFCS) scale, and 21% as level IV. All the children had mental retardation: 10 (7.5%) mild, 45 (33.3%) moderate and 78 (58.6%) severe. Most children (69.2%) with cerebral palsy did not speak, although 41 (30.8%) managed to utter single words and sentences. More than half (64.6%) required assistance in order to eat, whereas 47 (35.4%) had to be fed. Nearly half (44%) of the patients suffered from epilepsy. Periventricular leukomalacia and atrophy of the cerebral cortex were the most frequent findings on magnetic resonance imaging. Low birth weight, a low Apgar score, and preterm birth were factors that had a negative impact on the ability of children with cerebral palsy to ambulate independently. Spasticity of the lower limbs, mental retardation, lack of speech development and inability to eat without assistance, as well as changes observed on magnetic resonance imaging were also factors determining lack of independent walking.
Keywords: Non-ambulatory; cerebral palsy; children; risk factors